The IDOze Study: The Link Between Sleep Disruption and Tryptophan-Kynurenine Pathway Activation in Women With Human Immunodeficiency Virus . (8th July 2022) - Rogando, Andrea C; Weber, Kathleen M; Xing, Jiaqian; Xue, Xiaonan; Yohannes, Tsion; Morack, Ralph; Qi, Qibin; Clish, Clary; Bullock, Kevin; Gustafson, Deborah; Anastos, Kathryn; Sharma, Anjali; et al.
Abstract: Background: Poor sleep is associated with human immunodeficiency virus (HIV), particularly among women with HIV (WWH), although mechanisms are unclear. We explored cross-sectional associations between sleep disruption and tryptophan-kynurenine (T/K) pathway activation, measured by the kynurenine-to-tryptophan ratio (K:T). Methods: HIV-uninfected women (HIV – ) and WWH aged 35–70 years and on stable antiretroviral therapy were included. Sleep metrics were measured using wrist actigraphy. Plasma T/K pathway metabolites were measured using liquid chromatography–tandem mass spectrometry. Multivariate linear regression models examined relationships between K:T and actigraphy-based sleep metrics by HIV status. Results: WWH (n = 153) and HIV – women (n = 151) were demographically similar. Among WWH, median CD4 was 751 cells/µL; 92% had undetectable HIV RNA. Compared to HIV – women, WWH had higher K:T ( P < .001) and kynurenine ( P = .01) levels but similar tryptophan levels ( P = .25). Higher K:T was associated with more wake bouts ( P = .001), more time awake after sleep onset ( P = .01), and lower sleep efficiency ( P = .03) in WWH only. Conclusions: HIV infection was associated with T/K pathway activation; this activation was associated with poorer sleep efficiency and more fragmented sleep. While longitudinal studies are needed to elucidate the directionality of these associations, these findings may help identify treatments to reduce sleep disruption in WWH by targeting residual inflammation and T/K pathway activation. Abstract : Elevated kynurenine-to-tryptophan ratio, a measure of indoleamine 2, 3-dioxygenase activation, was associated with significantly poorer sleep efficiency and a greater number of wake episodes after sleep onset in women with HIV compared with demographically similar uninfected women.